Do changes in skull size of South American sea lions reflect changes in population density?. Issue 3 (20th February 2021) - Sosa Drouville, Ailin; Paschetta, Carolina; Crespo, Enrique Alberto; Grandi, María Florencia
Abstract: Populations of the South American sea lion (SASL, Otaria byronia ) have been intensely exploited for leather and oil in different parts of its distribution range throughout the 19th and 20th centuries, generating large changes in abundance. In Patagonia, the SASL population was reduced by more than 90% of its original abundance, and it began to recover after sealing ended. The aim of this work was to assess changes in size and shape of the skull related to changes in population abundance during the last 100 years. Using geometric morphometry techniques, we analyzed 145 individuals (68 males and 77 females) from Patagonia. Skulls were classified by sex, time period (harvest vs. postharvest), and decades of individual's birth. Results indicated that there were differences in skull size but not in shape discriminated by time period. Moreover, individuals of the postharvest period showed a decrease in the skull size during the last two decades, coinciding with the recovery in population abundance. Our results suggest the existence of a density‐dependence response in somatic growth of SASL population of Patagonia.